How marine upwelling influences the distribution of Artemesia longinaris (Decapoda: Penaeoidea)? - Sancinetti, Gustavo S. [UNESP]; Azevedo, Alexandre; Castilho, Antonio L. [UNESP]; Fransozo, Adilson [UNESP]; Costa, Rogério Caetano da [UNESP] (Univ Catolica De Valparaiso, 2014)
Upwelling events can occur in most of the oceans altering the water physical, chemical and sediment conditions and consequently the species communities dwelling the areas. For better understanding the behavior of populations inhabiting upwelling regions, the spatial and temporal distribution of a Penaeoidea shrimp was studied correlating it with the abiotic factors that vary during upwelling and non-upwelling periods in an area under influence of Cabo Frio upwelling. Bottom salinity and temperature, organic matter and sediment type from each station were sampled from March 2008 to February 2010, in six stations located between 5 and 45 m depth. The lowest temperatures were recorded during spring and summer for both years with temperature values lower than 19 degrees C. A total of 26,466 Artemesia longinaris shrimps were captured mainly in 10-35 m depth. Upwelling periods showed significant differences in abundance in relation to non-upwelling periods. The spatial distribution among stations varied according to the temperature with higher abundance in stations with values between 19 and 21 degrees C. The highest abundance of A. longinaris was recorded in spring and summer when intrusions of the cold waters of South Atlantic Central Waters (SACW) were frequent. Thus, the effect of cold water of SACW boosted by the upwelling was a determinant factor in the spatial and temporal distribution of A. longinaris in the studied region.
Keywords: Artemesia longinaris; Penaeoidea; distribution; environmental factors; SACW; Brazil; South Atlantic Ocean